ANALYSIS OF LEAD AND CADMIUM CONTENT IN JERUJU MANGROVE TEA LEAVES (Acanthus ilicifolius L.) WITH DIFFERENT DRYING TIMES - Kelibay, Amirula; Sulfiana, Sulfiana; Sukmawati, Sukmawati; Hardianti A, Fatimah; Rumwokas, Muhamad Saleh (Tanjungpura University, 2026)
Jeruju mangrove (Acanthus ilicifolius L.) is a coastal plant with potential for development as a herbal tea due to its bioactive compounds. However, its ability to accumulate heavy metals raises concerns regarding food safety. This study aimed to determine the lead (Pb) and cadmium (Cd) contents of jeruju herbal tea subjected to different drying times and to evaluate the effect of drying time on heavy metal levels. The study employed a Completely Randomized Design (CRD) with a single factor, namely drying time at 100 °C, consisting of three treatments (70, 85, and 100 min), with three replicates for each treatment. Pb and Cd contents were determined using Graphite Furnace Atomic Absorption Spectrometry (GFAAS) in accordance with the applicable SNI standards. The Pb content ranged from 3.37 to 4.78 mg/kg, with the highest concentration observed at 85 min and the lowest at 70 min. Analysis of variance showed a significant effect of drying time on Pb content (p < 0.05). In contrast, Cd was not detected in any treatment, indicating that its concentration was below the analytical method's detection limit. The results demonstrate that drying time affected Pb concentrations, whereas no detectable Cd was observed under the conditions investigated. These findings highlight the potential of jeruju leaves as a raw material for herbal tea while emphasizing the need for continued monitoring of Pb contamination to ensure product safety.